Energy consumption mechanism simulation and experimental study of reciprocating vibration for Chinese wolfberry picking - Mei, Song; Tang, Dunbing; Shi, Zhigang; Song, Zhiyu; Shen, Cheng (International Journal of Agricultural and Biological Engineering, 2024)
In order to find out the matching principle of excitation force and energy consumption of reciprocating vibrating Chinese wolfberry picking device, the energy consumption mechanism of reciprocating vibrating Chinese wolfberry picking device is studied. According to the structural characteristics and operating principle of the picking device, the no-load and load movement and force characteristics of the crank bearing and vibrating component are analyzed, and the theoretical model of energy consumption of the reciprocating vibration picking device is jointly constructed, and the simulation analysis is carried out. The results show that the vibrating component and load mass have a significant influence on torque, the load air resistance phase has a significant effect on torque, and the load air resistance and friction coefficient have no significant influence on torque. Subsequently, by building an AC servo motor torque detection system and a torque sensing detection system, verification experiments are carried out, the maximum torque of the preset system is 1.3 N∙m, the rated power is 400 W, the motor frequency is 20 Hz, the amplitude is 15 mm, and the total mass of the vibrating component is 0.143 kg. Test results show that, the no-load operation, the change trend of detected torque is consistent with simulation, the torque model is verified to be accurate. The maximum torque of simulation and detection are 0.52 N∙m and 0.57 N∙m respectively, and the error between test and simulation is 9.6%. For load operation, the maximum torque of five groups of branch loads of 20 g, 60 g, 100 g, 140 g, 180 g and 220 g are detected to be 0.73 N∙m, 0.74 N∙m, 0.75 N∙m, 0.82 N∙m and 0.83 N∙m, respectively, and the relationship model between load and torque is obtained by fitting. The research results can provide a theoretical basis which can configure a suitable motor in the reciprocating vibration Chinese wolfberry picking device with a certain load limit. Key words: Chinese wolfberry branches; vibration component; load; torque; power DOI: 10.25165/j.ijabe.20241704.8939 Citation: Mei S, Tang D B, Shi Z G, Song Z Y, Shen C. Energy consumption mechanism simulation and experimental study of reciprocating vibration for Chinese wolfberry picking. Int J Agric & Biol Eng, 2024; 17(4): 146–155.